Entre o singular e o plural: escre-vivendo mundos acadêmicos pelas letras de mulheres negras - Anna, Daniela Morais de Sant (2022)
This research focuses on the experience of black women in the academic context. To this end, we use as theoretical and methodological support the escrevivência (writing-experience) of Conceição Evaristo, which implies a production of knowledge necessarily loaded by the singular and collective constitutions that are imbricated in the body-experience of black women. The research includes six narratives started from the triggering question: "what is it like, was and/or has it been like to be a black woman in this academic context?” The general objective is to highlight, in the research and writing processes of these black women, the potency, the possibility of desacralizing these non-black academic places and to think the academy and education subverting the neutral, rigid and apolitical pretensions, as a practice of freedom, as bell hooks teaches us. We discuss the description of the academic context as it presents itself in the trajectory of black women as students and professors; we use Patricia Hill Collins' concept, Images of Control, to understand what and how images are developed that control this body-experience within the university scene and what are the ways of subverting and appropriating the control of the image itself that black feminism insurges upon. It ends with pedagogical clues that seek to affirm life and that necessarily go through processes that foster humanization, and not the opposite, and with Paulo Freire's and bell hooks' discussion about love, which underlie their educational praxis.